Dynamic Structural Analysis of Deployment of Scissors Structure in Space. Issue 1 (March 2013) - Takatsuka, Masao; Ohmori, Hiroshi
The objective of the present study is to investigate the dynamic motion of a deployable structure, which is composed of a scissors mechanism assumed to be deployed in space with a self-balancing moment by actuators. For this purpose, the present paper focuses on how to calculate the dynamic motion of deployment of the scissors mechanism in space with a self-balancing moment, in consideration of its mass and rotational friction around the joints, and showing its numerical results. The present paper also checks the stress and deflection of the frame, as a problem of the structural analysis of an unstable structure without outer boundaries.